2001
DOI: 10.1161/hc3101.092199
|View full text |Cite
|
Sign up to set email alerts
|

Eptifibatide and 7E3, but Not Tirofiban, Inhibit α v β 3 Integrin–Mediated Binding of Smooth Muscle Cells to Thrombospondin and Prothrombin

Abstract: Background-Our objective was to determine whether abciximab, eptifibatide, or tirofiban inhibited ligand binding to ␣ v ␤ 3 integrins on human aortic smooth muscle cells (HASMCs) or human umbilical vein endothelial cells (HUVECs). Abciximab binds ␣ IIb ␤ 3 on platelets and ␣ v ␤ 3 on HUVECs with similar affinity, whereas eptifibatide and tirofiban are thought to be highly specific for ␣ IIb ␤ 3 . The conclusion that eptifibatide does not bind vascular ␣ v ␤ 3 integrins may be premature, however, because recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 35 publications
3
45
0
2
Order By: Relevance
“…This finding is consistent with previous results showing that only ␣ v ␤ 3 -integrin blockade and not ␣ IIb ␤ 3 -integrin blockade was effective in reducing SMC migration. 23,24 In summary, our data support the conclusion that ␣ v ␤ 3 plays a critical role in SMC migration and neointimal lesion formation. The effectiveness of ␤ 3 -integrin deficiency is dependent on the severity of vascular injury, with benefit exhibited after nondisruptive arterial wall injury but not with donor bone marrow (*PϽ0.01), indicating that ␤ 3 ϩ/ϩ bone marrow (ie, ␤ 3 -integrin-expressing platelets) did not contribute to the inhibitory effect of ␤ 3 -integrin deficiency.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is consistent with previous results showing that only ␣ v ␤ 3 -integrin blockade and not ␣ IIb ␤ 3 -integrin blockade was effective in reducing SMC migration. 23,24 In summary, our data support the conclusion that ␣ v ␤ 3 plays a critical role in SMC migration and neointimal lesion formation. The effectiveness of ␤ 3 -integrin deficiency is dependent on the severity of vascular injury, with benefit exhibited after nondisruptive arterial wall injury but not with donor bone marrow (*PϽ0.01), indicating that ␤ 3 ϩ/ϩ bone marrow (ie, ␤ 3 -integrin-expressing platelets) did not contribute to the inhibitory effect of ␤ 3 -integrin deficiency.…”
Section: Discussionsupporting
confidence: 85%
“…SMC isolated from the aortas of SpragueDawley rats were cultured as previously described (11,18). Briefly, RASMC, passages 3-10, were grown to 70% subconfluence in serum-containing medium.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that TSP-1-stimulated SMCs or ␤ 3 integrin-expressing HEK cell proliferation is significantly inhibited by ␣ v ␤ 3 integrin blocking reagents. 34,35 Because the suppression of TSP-1-induced proliferation by the reagents was partial, receptors other than ␣ v ␤ 3 integrin may also be involved in TSP-1-stimulated signals, leading to proliferation. Our data suggest that together with ␤ 3 integrin, ␤ 1 integrin also appears to be involved in TSP-1-stimulated cell proliferation.…”
mentioning
confidence: 99%